Child malnutrition, infrastructure and income in Mexico - Edgardo A Ayala-Gaytán; Andrea Díaz Durán-Hernández (Instituto Nacional de Salud Pública, 2015)
Objective. Explain the variation in child malnutrition (CM), understood as low height for age (0 to 5 years old) for the period 1999-2006. Materials and methods. State estimations of child malnutrition and several indicators of subjacent probable causes of CM were employed, such as poverty indices, state product per capita, women scholar attainment and access to health and the sewage system. Panel data regression analysis with fixed and random effects were used to analyze the data. Results. The results indicate that the lack to access to health and sewage systems and poverty worsen CM, whereas women education helps to diminish CM. Conclusion. The study shows that infrastructure variables explain a significant part of the recent variation in DI across Mexican states, and that economic growth is not a sufficient condition to diminish DI.